Investigating the role of inhibition in human motor learning - Grigoras, IF (2022)
Motor learning is extremely important in everyday life: from learning how to reach and grab objects to learning complex movements, like driving a car or playing the piano, most daily activities and hobbies rely on previously acquired motor skills. Increasing evidence indicates that inhibition mediated by GABA, the most common inhibitory neurotransmitter, plays a key role in learning new motor skills. Modulating GABAergic inhibition may therefore influence motor learning.